Along Ukraine's River A Social and Environmental History of the Dnipro (Dnieper) - Cybriwsky, Roman Adrian 1945- (Central European University Press, 2018)
The River Dnipro (formerly better known by the Russian name of Dnieper) is linked intimately with the history and identity of Ukraine. Cybriwsky discusses the river as it was formed in nature and as it has been used and modified by human agency from ancient times to the present. From key vantage points along the river's course from its source in western Russia, through Belarus and Ukraine, to the Black Sea interesting stories shed light on past and present life in Ukraine. Pieces of Russian and Ukrainian literature that are set along the river are evoked, as well as various genres of song and landscape painting from various times in history. Topics include the legacy of Kyivan Rus, the period of Cossack dominion, the epic battles at the river in World War II, the building of dams and huge reservoirs by the Soviet Union, and the crisis of Chornobyl (Chernobyl). The book argues that the Dnipro and the farmlands along it are Ukraine's chief natural resources, and that the future of the country depends on putting both to good use. Written in informal style, with sparks of humor and without academic pretentiousness, the book is illustrated with original line drawings (maps) and photographs